Method for preparing high-whiteness low-chroma low-viscosity cellulose ether

By forming a complex with a high-viscosity cellulose ether and metal ions and oxidatively degraded, the problems of low-viscosity cellulose ether in the prior art are solved, and high whiteness and low yellowness are prepared in high whiteness and low yellowness.

CN119798469AActive Publication Date: 2025-04-11SHANDONG HEAD GRP CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510311490.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-17
Publication Date
2025-04-11
Estimated Expiration
2045-03-17

AI Technical Summary

Technical Problem

The prior art is difficult to effectively increase the whiteness of low-viscosity cellulose ethers and reduce their yellowness, and uneven molecular chains are easily generated during the degradation process, affecting product quality.

Method used

By forming a complex with high viscosity cellulose ether with metal ions, the generation of hydrogen bonds is reduced, the entry of oxidant is promoted, and oxidative degradation is carried out to form a short and uniform molecular chain. At the same time, cation exchange resin is used to remove metal ions, further improving the quality of the product.

Benefits of technology

The preparation of low viscosity cellulose ethers with high whiteness (87-92) and low yellowness (<3) is achieved, improving the quality and consistency of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119798469A_ABST
    Figure CN119798469A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of cellulose ether, in particular to a method for preparing high-whiteness, low-chroma and low-viscosity cellulose ether. The method for preparing the high-whiteness, low-chroma and low-viscosity cellulose ether comprises the following steps: firstly, matching high-viscosity cellulose ether with metal ions to form a complex, then carrying out oxidative degradation reaction on the complex under the action of hydrogen peroxide to obtain a low-viscosity cellulose ether coarse material, and finally, removing impurities, drying and grinding. The low-viscosity cellulose ether obtained through the preparation method is low in viscosity, the whiteness is 87-92, the yellowness is smaller than 3, and when a catalyst is added in the oxidative degradation process, the degradation reaction rate can be further increased, and the degradation reaction time can be further shortened. The low-viscosity cellulose ether has good quality and processability, and can be applied to the fields of coatings, paints, medicines, cosmetics and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of cellulose ethers, and in particular to a method for preparing cellulose ethers with high whiteness, low color and low viscosity. Background Art

[0002] The viscosity of cellulose ether has a great influence on the processing properties of cellulose ether. Among them, the molecular chain of low-viscosity cellulose ether is relatively short, the solubility in water is large, the fluidity is good, and it is easy to disperse and mix. Therefore, it has important applications in coatings, paints, medicines, cosmetics and other fields.

[0003] At present, there are two main methods for preparing low-viscosity cellulose ethers. One is to prepare it by etherification of low-molecular-weight alkaline cellulose, and the other is to degrade high-viscosity cellulose ethers. If low-molecular-weight alkaline cellulose is prepared by etherification, the refining process is more difficult, and the low-molecular-weight cellulose ether may be washed out, reducing the output rate of low-viscosity cellulose ethers. However, if low-viscosity cellulose ethers are obtained by degrading high-viscosity cellulose ethers, the degradation will be after refining, and the above problems will not occur.

[0004] The viscosity reduction method of high-viscosity cellulose ether can be achieved by adding inorganic acid, but in this way, the addition of inorganic acid and subsequent alkali neutralization during the viscosity reduction process increases the salt content of the product, and the acid smell may remain in the product, thus affecting the quality of the product. In addition, degradation can also be carried out by oxidation, but degradation is difficult to control and may produce more oxidation by-products, or the molecular chain length after degradation varies greatly, affecting the quality of low-viscosity cellulose ether, such as reduced whiteness, increased yellowness, and uneven quality.

[0005] The patent application document with publication number CN111344308A discloses the oxidative degradation of cellulose ether, which comprises adding an oxidant to a water-wet cellulose ether raw material, carrying out oxidative degradation at 20-100° C., then drying, and adding an alkaline salt to obtain low-viscosity cellulose ether. However, the obtained low-viscosity cellulose ether has a whiteness of 80-92 and a yellowness of 3.3, which means that the whiteness is relatively low and the yellowness is relatively high. Summary of the invention

[0006] In order to improve the whiteness and reduce the yellowness of low-viscosity cellulose ether, the present application provides a method for preparing high-whiteness, low-color and low-viscosity cellulose ether.

[0007] A method for preparing high-whiteness, low-chroma and low-viscosity cellulose ether comprises the following steps: S1: adding high viscosity cellulose ether to a metal salt solution, reacting at 50-70°C for 3-6h, washing with ethanol, and vacuum drying to obtain a cellulose ether metal complex; S2: adding the cellulose ether metal complex into a kneader, heating to 80-100° C., spraying in an aqueous hydrogen peroxide solution, stirring continuously for 2-8 hours, discharging the material, and obtaining a low-viscosity cellulose ether crude material; S3: Add low-viscosity cellulose ether crude material into deionized water, use cation exchange resin to remove cations, vacuum dry until the mass fraction of water in the material is less than 4.5%, and grind into powder.

[0008] In the above technical scheme, there are more hydroxyl groups, ether bonds, etc. in the high-viscosity cellulose ether macromolecular chain, especially when the degree of substitution is low, the cellulose ether molecules can form strong intermolecular hydrogen bonds, so that the intermolecular force is larger, and the high-viscosity cellulose ether generally has a higher molecular weight, a longer molecular chain, and the molecular chains are entangled with each other, and the steric hindrance is small, so the viscosity of the high-viscosity cellulose ether is larger and the solubility is reduced. When oxidative degradation is carried out, it is difficult for the oxidant molecules or the generated free radicals to enter the entangled molecular chains, and it is more conducive to attacking the ends of the molecular chains, so that the molecular chains of the degraded cellulose ether are uneven, affecting the quality of the product.

[0009] By forming a complex with high-viscosity cellulose ether and metal ions, the metal ions are coordinated with the oxygen in the hydroxyl group or ether bond of the high-viscosity cellulose ether, thereby reducing the generation of hydrogen bonds in the high-viscosity cellulose ether and weakening the hydrogen bonding effect in the cellulose ether molecules. The introduction of metal ions can increase the distance between molecules, which is more conducive to the entry of small molecules such as oxidants, thereby breaking the high-viscosity cellulose ether molecular chain and forming a shorter molecular chain. In addition, by adjusting the ratio of high-viscosity cellulose ether and metal ions, the number of coordination sites can be adjusted so that the coordination sites are relatively evenly distributed in the high-viscosity cellulose ether molecular chain, which is conducive to obtaining relatively uniform cellulose ether low-molecular chains. In addition, metal ions can also catalyze the decomposition of hydrogen peroxide by changing the valence, increase the decomposition rate of hydrogen peroxide, and thus increase the rate of oxidative degradation.

[0010] During the oxidative degradation process, the reaction temperature, reaction time and the amount of hydrogen peroxide added have an important influence on the degradation products. First, if the reaction temperature is too low, the decomposition rate of hydrogen peroxide is slow, and the oxidative degradation rate is slow. If the reaction temperature is too high, hydrogen peroxide may be ineffectively decomposed, so that the high-viscosity cellulose ether cannot be fully oxidatively degraded; secondly, as the reaction time increases, the oxidative degradation is more complete, but after the hydrogen peroxide is completely consumed, further oxidative degradation will not occur even if the reaction time is extended; finally, when the concentration of hydrogen peroxide in the reaction system is too high, excessive hydrogen peroxide may become a scavenger for the decomposed hydroxyl radicals, reacting with the hydroxyl radicals to generate oxygen and water, resulting in a decrease in hydroxyl radicals, a slow oxidative degradation rate, and an inability to fully degrade the high-viscosity cellulose.

[0011] Deionized water is added to the low-viscosity cellulose ether crude material, the low-viscosity cellulose ether is dissolved in the water, and the metal cations are removed through the cation exchange resin to reduce the impact of impurities on product quality.

[0012] Preferably, the high viscosity cellulose ether in step S1 is one or more of carboxymethyl cellulose, hydroxypropyl cellulose, hydroxypropyl methyl cellulose, hydroxyethyl methyl cellulose and hydroxyethyl cellulose.

[0013] Preferably, the viscosity of the aqueous solution of the high viscosity cellulose ether prepared in step S1 with a mass fraction of 2% is 5000-50000 mPa•s.

[0014] Preferably, the metal salt in step S1 is one of an iron salt, a copper salt and a cobalt salt.

[0015] Preferably, in step S1, the mass ratio of the high viscosity cellulose ether to the metal salt is 100:(10-30).

[0016] Preferably, in step S2, the mass ratio of the cellulose ether metal complex to hydrogen peroxide is 100:(1-10).

[0017] In the above technical solution, the amount of hydrogen peroxide added has a great influence on the quality of the low-viscosity cellulose ether produced. If the amount of hydrogen peroxide added is too little, the whiteness is low, the yellowness increases, and the viscosity is high, and the reaction time is also prolonged. If the amount of hydrogen peroxide added is too much, the hydrogen peroxide cannot be fully utilized, and the high-viscosity cellulose ether cannot be fully degraded.

[0018] Further preferably, in step S2, a catalyst is also added, and the preparation method of the catalyst comprises the following steps: Add MCM-48 molecular sieve to the precursor solution of metal active components, ultrasonically impregnate for 1-3 hours, dry at 100-120° C. for 3-6 hours, place in a muffle furnace and roast at 450-650° C. for 1-3 hours to obtain the product.

[0019] In the above technical solution, the metal active components are loaded on a molecular sieve with a large surface area so that the metal active components are evenly dispersed on the carrier, which can catalyze the decomposition of hydrogen peroxide, increase the oxidative degradation rate, reduce the generation of by-products, and improve the quality of the product.

[0020] Preferably, the metal active component is one or more of copper oxide, iron oxide and cobalt oxide.

[0021] Preferably, the mass ratio of the MCM-48 molecular sieve to the precursor of the metal active component is 1:(0.1-0.25).

[0022] Preferably, the mass ratio of the cellulose ether metal complex to the catalyst is 100:(0.1-1).

[0023] The above technical solution of the present application includes at least the following beneficial effects: 1. In the present application, high-viscosity cellulose ether is coordinated with metal ions to form a cellulose ether metal complex with a certain number of coordination sites, which is conducive to the subsequent degradation into low-viscosity cellulose ether with relatively uniform molecular chain length, thereby improving whiteness and reducing yellowness.

[0024] 2. The present application uses molecular sieves to load metal active components, which serve as catalysts for the decomposition of hydrogen peroxide during the degradation process, thereby increasing the decomposition rate of hydrogen peroxide, increasing the degradation rate of high-viscosity cellulose ethers, and improving the quality of the product.

[0025] 3. The low-viscosity cellulose ether obtained by the preparation method of the present application has a whiteness of 87-92 and a yellowness of <3. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is the viscosity of a 2% aqueous solution prepared from high-viscosity cellulose ether raw materials and low-viscosity cellulose ether; Figure 2 It is the whiteness and yellowness of low viscosity cellulose ether. DETAILED DESCRIPTION

[0027] The present application is further described in detail below with reference to the embodiments.

[0028] Unless otherwise specified, the raw materials used in the examples and comparative examples of the present application are all commercially available.

[0029] Example Example 1 The method for preparing high-whiteness, low-chroma and low-viscosity cellulose ether of this embodiment comprises the following steps: S1: Weigh 500 g of carboxymethyl cellulose, add 5000 g of 1% ferric chloride aqueous solution, react at 50° C. for 6 h, wash the product with 80% ethanol solution by volume, put it in a vacuum drying oven, and dry it at 50° C. to obtain a cellulose ether metal complex; S2: Weigh 1 kg of cellulose ether metal complex, add it into a kneader, start stirring, raise the temperature to 80°C, spray in 50 g of 20% by mass hydrogen peroxide aqueous solution, stir continuously for 8 hours, and discharge to obtain a low-viscosity cellulose ether crude material; S3: dissolving the above-mentioned low-viscosity cellulose ether crude material in deionized water, using a cation exchange resin to remove metal cations, vacuum drying until the mass fraction of water in the material is less than 4.5%, and grinding.

[0030] Example 2 The method for preparing high-whiteness, low-chroma and low-viscosity cellulose ether of this embodiment comprises the following steps: S1: Weigh 500 g of hydroxypropyl cellulose, add 5000 g of 3% cobalt chloride aqueous solution, react at 70° C. for 3 h, wash the product with 80% ethanol solution by volume, put it in a vacuum drying oven, and dry it at 50° C. to obtain a cellulose ether metal complex; S2: Weigh 1 kg of cellulose ether metal complex, add it into a kneader, start stirring, heat to 100°C, spray 50 g of 20% by mass hydrogen peroxide aqueous solution, stir continuously for 2 hours, discharge the material, and obtain a low-viscosity cellulose ether crude material; S3: dissolving the above-mentioned low-viscosity cellulose ether crude material in deionized water, using cation exchange resin to remove metal cations, vacuum drying until the mass fraction of water in the material is less than 4.5%, and grinding.

[0031] Example 3 The method for preparing high-whiteness, low-chroma and low-viscosity cellulose ether of this embodiment comprises the following steps: S1: Weigh 500 g of hydroxypropyl methylcellulose, add 5000 g of 2% copper chloride aqueous solution, react at 60° C. for 5 h, wash the product with 80% ethanol solution by volume, put it into a vacuum drying oven, and dry it at 50° C. to obtain a cellulose ether metal complex; S2: Weigh 1 kg of cellulose ether metal complex, add it into a kneader, start stirring, raise the temperature to 90°C, spray in 50 g of 20% by mass hydrogen peroxide aqueous solution, stir continuously for 5 hours, and discharge to obtain a low-viscosity cellulose ether crude material; S3: dissolving the above-mentioned low-viscosity cellulose ether crude material in deionized water, using a cation exchange resin to remove metal cations, vacuum drying until the mass fraction of water in the material is less than 4.5%, and grinding.

[0032] Example 4 The method for preparing high-whiteness, low-chroma and low-viscosity cellulose ether in this embodiment is different from that in Example 3 in that: S2: Weigh 100 g of cellulose ether metal complex and 200 mL of deionized water, stir evenly, heat to 90° C., spray 50 g of 20% by mass hydrogen peroxide aqueous solution, stir continuously for 5 h, and discharge to obtain a low-viscosity cellulose ether crude material; The remaining steps are the same as those in Example 3.

[0033] Example 5 The method for preparing high-whiteness, low-chroma and low-viscosity cellulose ether in this embodiment is different from that in Example 3 in that: S2: Weigh 100 g of cellulose ether metal complex and 200 mL of deionized water, stir evenly, heat to 90° C., spray 30 g of 20% by mass hydrogen peroxide aqueous solution, stir continuously for 5 h, and discharge to obtain a low-viscosity cellulose ether crude material; The remaining steps are the same as those in Example 3.

[0034] Example 6 The method for preparing high-whiteness, low-chroma and low-viscosity cellulose ether in this embodiment is different from that in Example 5 in that: S2: Weigh 1 kg of cellulose ether metal complex and 1 g of catalyst, add them into a kneader, start stirring, raise the temperature to 90°C, spray 300 g of 20% by mass hydrogen peroxide aqueous solution, stir continuously for 3 hours, discharge, and obtain a low-viscosity cellulose ether crude material; S3: dissolving the above-mentioned low-viscosity cellulose ether crude material in deionized water, filtering to remove the catalyst, using a cation exchange resin to remove metal cations, vacuum drying until the mass fraction of water in the material is less than 4.5%, and grinding into powder; The remaining steps are the same as those in Example 5; The preparation method of the catalyst in this embodiment comprises the following steps: Weigh 20 g of a 5% cobalt chloride aqueous solution, add 10 g of MCM-48 molecular sieve, ultrasonically impregnate for 1 h, dry at 100 ° C for 6 h, place in a muffle furnace and calcine at 450 ° C for 3 h to obtain.

[0035] Example 7 The method for preparing high-whiteness, low-chroma and low-viscosity cellulose ether in this embodiment is different from that in Example 5 in that: S2: Weigh 1 kg of cellulose ether metal complex and 10 g of catalyst, add them into a kneader, start stirring, raise the temperature to 90°C, spray in 300 g of 20% by mass hydrogen peroxide aqueous solution, stir continuously for 3 h, discharge, and obtain a low-viscosity cellulose ether crude material; S3: dissolving the above-mentioned low-viscosity cellulose ether crude material in deionized water, filtering to remove the catalyst, using a cation exchange resin to remove metal cations, vacuum drying until the mass fraction of water in the material is less than 4.5%, and grinding into powder; The remaining steps are the same as those in Example 5; The preparation method of the catalyst in this embodiment comprises the following steps: Weigh 50 g of 5% ferric chloride aqueous solution, add 10 g of MCM-48 molecular sieve, ultrasonically impregnate for 3 h, dry at 120 ° C for 3 h, place in a muffle furnace and calcine at 650 ° C for 1 h to obtain.

[0036] Comparative Example Comparative Example 1 The method for preparing high-whiteness, low-color and low-viscosity cellulose ether of this comparative example comprises the following steps: Weigh 1 kg of hydroxypropyl methylcellulose, add it to a kneader, start stirring, raise the temperature to 90°C, spray in 50 g of a 20% by mass hydrogen peroxide solution, stir continuously for 5 hours, vacuum dry until the mass fraction of moisture in the material is less than 4.5%, and grind into powder.

[0037] Performance testing 1. Viscosity detection The high-viscosity cellulose ether raw materials of Examples 1-7 and Comparative Example 1 and the prepared low-viscosity cellulose ether were respectively prepared into aqueous solutions with a mass fraction of 2%, and the viscosity at room temperature was measured using a rotational viscometer. The results are as follows: Figure 1 shown.

[0038] 2. Whiteness and yellowness detection According to ASTM E313 standard, the whiteness and yellowness of low viscosity cellulose ether are measured. The higher the yellowness, the more obvious the color difference and the higher the chroma. The results are as follows: Figure 2 shown.

[0039] Results Analysis from Figure 1 It can be seen from the data of Comparative Example 1 and the examples that the high-viscosity cellulose ether is more easily degraded and has a lower viscosity after being combined with metal ions. It can also be seen from the data of the comparative examples that with the increase in the amount of hydrogen peroxide added, the viscosity of the low-viscosity cellulose ether first decreases significantly and then remains basically unchanged. Moreover, after the catalyst is added, the viscosity of the low-viscosity cellulose ether decreases to a certain extent.

[0040] from Figure 2 It can be seen from the data that after the high-viscosity cellulose ether is combined with metal ions, the whiteness is greatly improved and the yellowness is reduced, indicating that the quality of the low-viscosity cellulose ether obtained is better; in addition, with the increase of the amount of hydrogen peroxide added, the whiteness is improved and the yellowness is reduced, but after reaching a certain value, it remains basically unchanged.

[0041] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A method for preparing high-whiteness, low-color and low-viscosity cellulose ether, characterized in that: The steps include: S1: adding high viscosity cellulose ether to a metal salt solution, reacting at 50-70°C for 3-6h, washing with ethanol, and vacuum drying to obtain a cellulose ether metal complex; S2: adding the cellulose ether metal complex into a kneader, heating to 80-100° C., spraying in an aqueous hydrogen peroxide solution, stirring continuously for 2-8 hours, discharging the material, and obtaining a low-viscosity cellulose ether crude material; S3: Add low-viscosity cellulose ether crude material into deionized water, use cation exchange resin to remove cations, vacuum dry until the mass fraction of water in the material is less than 4.5%, and grind into powder.

2. The method for preparing high-whiteness, low-color and low-viscosity cellulose ether according to claim 1, characterized in that: The high viscosity cellulose ether in step S1 is one or more of carboxymethyl cellulose, hydroxypropyl cellulose, hydroxypropyl methyl cellulose, hydroxyethyl methyl cellulose and hydroxyethyl cellulose.

3. The method for preparing high-whiteness, low-color and low-viscosity cellulose ether according to claim 1, characterized in that: The viscosity of the aqueous solution of the high viscosity cellulose ether prepared in step S1 with a mass fraction of 2% is 5000-50000 mPa•s.

4. The method for preparing high-whiteness, low-color and low-viscosity cellulose ether according to claim 1, characterized in that: The metal salt in step S1 is one of iron salt, copper salt and cobalt salt.

5. The method for preparing high-whiteness, low-color and low-viscosity cellulose ether according to claim 1, characterized in that: In step S1, the mass ratio of the high viscosity cellulose ether to the metal salt is 100:(10-30).

6. The method for preparing high-whiteness, low-color and low-viscosity cellulose ether according to claim 1, characterized in that: In step S2, the mass ratio of the cellulose ether metal complex to hydrogen peroxide is 100:(1-10).

7. The method for preparing high-whiteness, low-color and low-viscosity cellulose ether according to claim 1, characterized in that: In step S2, a catalyst is also added, and the preparation method of the catalyst comprises the following steps: Add MCM-48 molecular sieve to the precursor solution of metal active components, ultrasonically impregnate for 1-3 hours, dry at 100-120° C. for 3-6 hours, place in a muffle furnace and roast at 450-650° C. for 1-3 hours to obtain the product.

8. The method for preparing high-whiteness, low-color and low-viscosity cellulose ether according to claim 7, characterized in that: The metal active component is one or more of copper oxide, iron oxide and cobalt oxide.

9. The method for preparing high-whiteness, low-color and low-viscosity cellulose ether according to claim 7, characterized in that: The mass ratio of the MCM-48 molecular sieve to the precursor of the metal active component is 1:(0.1-0.25).

10. The method for preparing high-whiteness, low-color and low-viscosity cellulose ether according to claim 7, characterized in that: The mass ratio of the cellulose ether metal complex to the catalyst is 100:(0.1-1).

Citation Information

Patent Citations

  • Oxidative degradation of cellulose ethers

    CN111344308A

  • Method for producing cellulose ether derivative

    CN101835805A

  • Simplified process for making low viscosity cellulose ether

    CN111344309A

  • Process for the manufacture of low viscosity water-soluble cellulose ethers

    GB1139637A

  • Simplified process for making low viscosity cellulose ether

    US20200255547A1